PERENCANAAN BANGUNAN PENGENDALI SEDIMEN DI KALI KREO - Andrey Suryanto; Thomas Resa Putra; Suripin Suripin; Salamun Salamun (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The land use change of area sub-watershed Kreo potentially lead to an increase in erosion and sediment transport by river flow increases. Increased sediment transport in river flow can destabilize the river morphology Kreo such as a decrease in the riverbed Kreo (degradation), changes in river geometry vertical and horizontal direction, and the elevation of the riverbed (agradastion). To control the morphology of the river Kreo stability it need to be built sediment control structure (check dam). The design of sedimen control at Kreo river is located in the Village of Kali Pancur, District Ngaliyan. Kreo river have watershed area 65.58 km2 the length of the main river ± 30.60 km, the average river width of 14.6 m. Based on the calculations have been done better hydrological analysis, hydraulics analysis, planning dimensions check dams, control stability of main dam, and capacity analysis of sediment the river discharge plan obtained by 102 m3/s, check dam spillway base width of 20.5 m, effective height of the main dam 2 m, foundation depth of main dam, thick of mercu main dam 1.5 m, length of basin whirl 17 m, thick of basin whirl 0,6 m and sediment capacity is 14,911,55 m3 with the design life of 10.7 years. This project implementation is scheduled for 20 weeks with a budget plan of Rp. 2.340.000.000, -.